EKSPLORASI ETNOMATEMATIKA PADA KERAJINAN KAYU DI DESA TUTUL KECAMATAN BALUNG SEBAGAI BAHAN AJAR GEOMETRI - Kholifatuzzuhro, Aina; Sunardi, Sunardi; Monalisa, Lioni Anka (Department of Mathematics Education , University of Jember, 2020)
This study aims to explore anything ethnomatematics related to woodwork in Tutul Village, Jember. Woodcraft is a craft made from wood. This type of research is a study using a qualitative approach with ethnographic design. Research subjects in this study were craftsmen and owners of